A Review of Self-Healing Concrete Using Bacillus Bacteria as Healing Agent on Compressive Strength of Concrete - Azizi, Nur Fatihah; Mokhtar, Norfaniza (Recent Trends in Civil Engineering and Built Environment, 2024)
Bio concrete or bio influenced self-healing concrete is a product which has the ability to heal concrete by producing chemical reaction from intentionally mixing the micro-organism into the concrete. When cracks are produced, water seeps into the cracks and activates the present dormant micro-organism. These micro-organisms later produce mineral that will fill the cracks. The main objective of this study is to investigate the effect of bacteria as a self-healing agent on concrete and to identify the most factors effect self-healing in bio-concrete using bacteria through case study. In this study, the systematic review used to evaluate the effect of bacteria in concrete structure as self-healing agent. It undergoes a few processes to get the suitable article to use for this study. From previous study, the method used is Compressive Strength Test to confirmed that bacteria have ability to precipitate calcium carbonate. From this study, it helps to identify the effect of bacteria on concrete as self-healing agent.